PEMBELAJARAN SAINS BERBASIS POTENSI LOKAL UNTUK MENINGKATKAN LITERASI SAINS DAN MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Marheni Rayung Puspaningrum; Arina Wanawati; Devi Anggi Friani; Seprie (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine the effectiveness of local-potential-based science learning in improving science literacy and learning motivation of fifth-grade elementary school students. A quasi-experimental design with pretest-posttest control group was employed, involving 63 students divided into experimental and control groups. Data were collected using science literacy tests and a five-point Likert scale questionnaire on learning motivation. Descriptive and inferential statistical analyses, including independent sample t-tests and ANCOVA, were conducted to analyze the data. The results showed that students in the experimental group achieved significantly higher posttest scores (M = 82.63, SD = 7.54) than the control group (M = 72.18, SD = 8.11), with a large effect size (Cohen’s d = 1.05). ANCOVA confirmed that the difference remained significant after controlling for pretest scores (F = 33.97; p < 0.001), indicating that local-potential-based learning substantially contributed to students’ science literacy. Moreover, learning motivation increased markedly in the experimental group (M = 4.21) compared to the control group (M = 3.62) with a large effect size (d = 0.86). The findings suggest that integrating local environmental contexts into science learning enhances both cognitive and affective outcomes in elementary science education